2017
DOI: 10.14336/ad.2017.0110
|View full text |Cite
|
Sign up to set email alerts
|

Parity History Determines a Systemic Inflammatory Response to Spread of Ovarian Cancer in Naturally Aged Mice

Abstract: Aging intersects with reproductive senescence in women by promoting a systemic low-grade chronic inflammation that predisposes women to several diseases including ovarian cancer (OC). OC risk at menopause is significantly modified by parity records during prior fertile life. To date, the combined effects of age and parity on the systemic inflammation markers that are particularly relevant to OC initiation and progression at menopause remain largely unknown. Herein, we profiled a panel of circulating cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 81 publications
4
22
0
Order By: Relevance
“…27 It has been reported that parity has a longterm, tumor-concurrent effect on inflammation markers at menopause which might be a contributing factor in decreasing the OC risk. 28 One explanation for this finding is that child-bearing might reduce immunosuppression (which typically allows tumor spread) and thus counteract aging-associated systemic inflammation. 28 A previous study about the combined effects of age and parity on the systemic inflammation markers relevant to OC initiation revealed two mechanisms responsible for this protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 It has been reported that parity has a longterm, tumor-concurrent effect on inflammation markers at menopause which might be a contributing factor in decreasing the OC risk. 28 One explanation for this finding is that child-bearing might reduce immunosuppression (which typically allows tumor spread) and thus counteract aging-associated systemic inflammation. 28 A previous study about the combined effects of age and parity on the systemic inflammation markers relevant to OC initiation revealed two mechanisms responsible for this protection.…”
Section: Discussionmentioning
confidence: 99%
“…28 One explanation for this finding is that child-bearing might reduce immunosuppression (which typically allows tumor spread) and thus counteract aging-associated systemic inflammation. 28 A previous study about the combined effects of age and parity on the systemic inflammation markers relevant to OC initiation revealed two mechanisms responsible for this protection. These mechanisms are the decreased stimulation of regulatory B-cells and the partial impairment of the M2 shift in tumor-associated macrophages observed in multiparous aged mice compared with virgin aged mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study with female C57BL/6 mice was approved by the Bioethics Committee, Faculty of Medicine, University of Chile (CBA # 0536 FMUCH). The care and monitoring of the two experimental groups, virgin and multiparous, have recently been described in detail [18]. Figure 1A depicts the experimental design for the present report.…”
Section: Animals Study Scheme and Sample Collectionmentioning
confidence: 99%
“…Mouse models have been used to study OC risk factors, including obesity [15], inflammation [16], age [8], and genetic inheritance [17], among others. Continuing the recent work on peritoneal tumor spread and systemic inflammation in an aged syngeneic female C57BL/6 mouse model of OC maintained in multiparous and nulliparous regimens [18], here, we studied the effect of parity history on the ovarian transcriptome in intact, uninduced animals. Increased transcript levels of several markers of oocytes and follicles concomitant with significantly higher residual follicle counts were observed in multiparous ovaries.…”
Section: Introductionmentioning
confidence: 99%